The relationships between leptin levels in maternal serum and breast milk of mothers and term infants - Yilmaz, Feray Cagiran; Ozcelik, Ayse Ozfer (Taylor & Francis Ltd, 2021)
Background Leptin in breast milk play a significant role in metabolic programming. Objective The aim of this study to evaluate the relationship between leptin levels in maternal serum and breast milk, and certain anthropometric measurements of infants and mothers. Methods This study was conducted with 65 females and term infants. Anthropometric measurements of the mothers and the infants were obtained on the first, third, and sixth months, and leptin levels in maternal serum and breast milk were measured. Results In this study, leptin levels in breast milk were positively correlated with leptin levels in maternal serum while the leptin levels in breast milk were lower than the serum leptin levels. It was also determined that mothers' body weights, BMI values, waist and hip circumferences were increased in a statistically significant way in terms of the months (p < .001). It was discovered that all the anthropometric measurements of the mothers were positively correlated with leptin levels in breast milk and maternal serum in all the months (p < .001). Furthermore, it was determined that the body weights of the infants in certain months were negatively correlated with leptin levels in breast milk and maternal serum while the lengths of the infants were positively correlated with leptin levels in breast milk and maternal serum (p < .05). Conclusions This study was determined that leptin levels in breast milk and maternal serum were related to anthropometric measurements of both mothers and infants. Future studies with larger populations are needed to understand the long-term consequences of leptin metabolism comprehensively. Key messages This study was determined that breast milk leptin level and maternal serum leptin level demonstrated a positive correlation, and breast milk leptin level was lower than maternal serum leptin level. Mothers' anthropometric measurements were positively correlated with leptin levels in breast milk and maternal serum in all the months. There was mostly a negative correlation between breast milk leptin level and infant body weight.
Keywords: Breast milk; anthropometry; infant; nutrition status; leptin